Design of The 3D Animation Film "Bully" as an Educational Media about The Dangers of Bullying in Elementary School Children - Damar Ketawang; M. Bintang Trimaulana; Moses Raissa Graceivan (Jurnal Info Sains : Informatika dan Sains, 2026)
The 3D animated film “Bully” is designed as an educational medium to raise awareness of elementary school students about bullying, a serious problem in educational institutions that negatively affects both the victim and the learning environment. Through interesting animations and relevant stories, this movie conveys educational messages for children. The manufacturing process uses the Research and Development (R&D) method which includes problem identification, concept development, production, feasibility testing, and distribution. A survey at SDN 139 Palembang showed that many students experienced bullying, both verbal and physical, with the psychological impact felt the most. This movie aims to foster empathy, provide solutions to prevent bullying, and contribute to the creative industry. The animation is expected to be an effective medium in delivering moral and educational messages that are easy for children to understand.